Design of a Nutrient and Environment Monitoring IoT Device in Vertical Hydroponic System - Linelson, Ricardo; Saputri, Fahmy Rinanda (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2025)
This study presents the design and performance evaluation of an Internet of Things (IoT)-based nutrient and environmental monitoring device for vertical hydroponic farming. The system employs multiple sensors to measure pH, Total Dissolved Solids (TDS), nutrient temperature, air temperature, and air humidity. Data are transmitted via ESP32 and integrated with the Arduino IoT Cloud, enabling real-time monitoring through a web dashboard and IoT Remote mobile application. A 10-day testing period was conducted to compare sensor outputs against standard calibrator references. The device demonstrated minimal bias (e.g., 0.20 for pH, 0.51